Status of the neuromyelitis optica spectrum disorder in Latin America - Rivera, Victor M.; Hamuy, Fernando; Rivas, Veronica; Gracia, Fernando; Ignacio Rojas, Juan; Bichuetti, Denis Bernardi; Maria Villa, Andres; Marques, Vanessa Daccah; Soto, Arnoldo; Bertado, Brenda; Trevino Frenk, Irene; Galleguillos, Lorna; et al. (My University, 2021)
Background: Neuromyelitis optica spectrum disorders (NMOSD) is an increasing diagnostic and therapeutic challenge in Latin America (LATAM). Despite the heterogeneity of this population, ethnic and socioeconomic commonalities exist, and epidemiologic studies from the region have had a limited geographic and population outreach. Identification of some aspects from the entire region are lacking. Objectives: To determine ethnic, clinical characteristics, and utilization of diagnostic tools and types of therapy for patients with NMOSD in the entire Latin American region. Methods: The Latin American Committee for Treatment and Research in MS (LACTRIMS) created an exploratory investigational survey addressed by Invitation to NMOSD Latin American experts identified through diverse sources. Data input closed after 30 days from the initial invitation. The questionnaire allowed use of absolute numbers or percentages. Multiple option responses covering 25 themes included definition of type of practice; number of NMOSD cases; ethnicity; utilization of the 2015 International Panel criteria for the diagnosis of Neuromyelitis optica (IPDN); clinical phenotypes; methodology utilized for determination of anti-Aquaporin-4 (anti-AQP4) antibodies serological testing, and if this was performed locally or processed abroad; treatment of relapses, and long-term management were surveyed. Results: We identified 62 investigators from 21 countries reporting information from 2154 patients (utilizing the IPDN criteria in 93.9% of cases), which were categorized in two geographical regions: North-Central, including the Caribbean (NCC), and South America (SA). Ethnic identification disclosed Mestizos 61.4% as the main group. The most common presenting symptoms were concomitant presence of optic neuritis and transverse myelitis in 31.8% (p=0.95); only optic neuritis in 31.4% (more common in SA), p<0.001); involvement of the area postrema occurred in 21.5% and brain stem in 8.3%, both were more frequent in the South American cases (p<0.001). Anti-AQP4 antibodies were positive in 63.9% and anti-Myelin Oligodendrocyte Glycoprotein (MOG) antibodies in 4.8% of total cases. The specific laboratorial method employed was not known by 23.8% of the investigators. Acute relapses were identified in 81.6% of cases, and were treated in 93.9% of them with intravenous steroids (IVS); 62.1% with plasma exchange (PE), and 40.9% with intravenous immunoglobulin-G (IVIG). Therapy was escalated in some cases due to suboptimal initial response. Respondents favored Rituximab as long-term therapy (86.3%), whereas azathioprine was also utilized on 81.8% of the cases, either agent used indistinctly by the investigators according to treatment accessibility or clinical judgement. There were no differences among the geographic regions. Conclusions: This is the first study including all countries of LATAM and the largest cohort reported from a multinational specific world area. Ethnic distributions and phenotypic features of the disease in the region, challenges in access to diagnostic tools and therapy were identified. The Latin American neurological community should play a determinant role encouraging and advising local institutions and health officials in the availability of more sensitive and modern diagnostic methodology, in facilitating the the access to licensed medications for NMOSD, and addressing concerns on education, diagnosis and management of the disease in the community.
Keywords: neuromyelitis optica; latin america; diagnosis; therapy; socioeconomic aspects